PENGEMBANGAN APLIKASI INFORMASI JADWAL PELAYANAN PENDETA BERBASIS ANDROID - Jenni Veronika Ginting (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
The development of this application is designed to make it easier for Churches, Pastors and Moderamen to see the pastor's ministry schedule in detail. With a large number of pastors scattered in the Moderamen service area both from Sabang to Merauke, which consists of Klasis and Runggun. The information application for android-based pastor GBKP service schedule is an application that can display a list of pastor services, a list of pastors 'names that are intended for all GBKP congregations to facilitate the dissemination of information on pastors' service schedules. Scheduling is very important for designing and managing a system consisting of a number of activities with limited resources.